PENERAPAN SISTEM INFORMASI AKADEMIK BERBASIS WEB MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT - Fitriani, Eka; Royadi, Royadi; Ardiansyah, Dian; Saepudin, Atang; Aryanti, Riska (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
The world of technology is advancing rapidly in all fields every day, including education. Systems that support information delivery are now presented in applications or web platforms. SMK Negeri Pertanian requires an adequate information system to convey academic information to students and teachers and to manage student data at the school. To address this issue, it is necessary to implement a web-based academic information system at SMK Negeri Pertanian using the Rapid Application Development (RAD) method for system development. The Rapid Application Development (RAD) method was chosen because it emphasizes speed and flexibility, allowing the application to be completed more quickly. The developed academic information system will manage and display information such as teacher data, student data, subject data, grades, teaching schedules, and other academic-related information. The result of this implementation is an effective and efficient web-based information system for delivering academic information to students and teachers.